Some Aspects of the Impact of Invasive Plants in Romania - Dobrescu, Codruța Mihaela; Turtureanu, Anca; Dorobat, Leonard Magdalin (Journal of Danubian Studies and Research, 2022)
In a larger or smaller geographical area, before human activity intervened, the distribution of plant and animal species is the result of hundreds of millions of years of evolution. Through various anthropogenic activities, this distribution has been greatly disrupted, introducing intentionally or unintentionally a number of plant or animal species in geographical areas where they would not have existed without human intervention. So this ecological balance achieved by nature in millions of years, in geological times, is threatened and destroyed by man in a very short time, years or at most decades. There is no single, unanimously accepted definition of invasive species. Most agree that the invasive species is introduced into a geographical area other than the one from which the species originated and, as a result, this species finds the conditions to spread at high speed, to the detriment of some native species, generating ecosystem problems, sometimes very large. Other specialists make a clear difference in terms of non-native species, calling exotic species, those that are present in new ecosystems, do not cause disturbances and invasive species, ie species that reach other ecosystems, cause their dysfunctions. As for invasive plants, they obviously do not have their own mobility and their invasive appearance is less obvious than in the case of invasive animal species. However, the effects of these invasive plants are often severe, and are not limited to ecological aspects but, directly or indirectly, the effects can be even serious at the economic level or in terms of human health. The Research Institute for Nature and Forest (INBO) and the Center for Ecology and Hydrology (CEH) have compiled an inventory (DAISIE - Delivering Alien Invasive Species Inventories for Europe) which currently contains 12104 allogeneic taxa for Europe. This was made possible by an international effort involving more than 300 researchers and funded by European funds. The database is constantly updated, with over 1650 experts constantly working on this issue. The severity of this phenomenon is illustrated by the difficult to estimate costs of invasive species, in Europe the accounting of these costs being earlier, but they are tens of billions of euros annually. By comparison, combating invasive species costs the United States more than 80 billion euros a year. Romania is no exception, the problem of invasive plants being a very important aspect with negative implications for the economy and the quality of human life.